Control Study of Hydropower System with Francis Turbine in Isolated Operation - Usha Adhikari; Pramish Shrestha; Bernt Lie (Modeling, Identification and Control)
This paper provides a comprehensive examination of controller design for hydropower systems equipped with Francis turbines operating in isolated conditions. By employing a mechanistic modelling approach using differential algebraic equations, the study captures the complex interplay of hydraulic, mechanical, and electrical subsystems, enabling an in-depth analysis of system dynamics under varying load conditions. A two-step approach is adopted, where a PID controller is initially designed for a linearized model and subsequently tested on a nonlinear model, allowing for a systematic evaluation of its performance, in accordance with the Norwegian Transmission System Operator specifications. The controller design process emphasizes achieving critical stability margins, meeting industry standards, and addressing the challenges posed by nonlinear system behaviour. The novelty of this work lies in the use of a recently developed Francis turbine model, its application to a real-world hydropower plant using realistic parameters, and the presentation of the controller design from a control engineering perspective. Directions for future work include exploring optimization-based controller designs, incorporating realistic load profiles, and refining system model to address complex real-world scenarios.